2007
DOI: 10.1299/jmmp.1.564
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Functionality of Nano-Precipitated Calcium Carbonate as Filler in Thermoplastics

Abstract: This research aims to investigate the functionality of nano-precipitated calcium carbonate (NPCC) as filler in thermoplastic resins based on property enhancement. Three types of thermoplastics were used: polyethylene (PE), polypropylene (PP) and polyvinyl chloride (PVC). The resins were evaluated by determining the effect of different NPCC loading on the chemical structure, thermal and mechanical properties of thermoplastics. Results showed that there was an interfacial bonding with the NPCC surface and the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…There is also a decreasing trend in impact strength with increasing CaCO3 content. This trend has also been observed by Basilia et al [3] with different matrices. Increased stiffness and hardness caused by filler presence may have favoured crack propagation upon impact, and composite specimen will absorb less energy than the neat polymer, causing a more brittle behaviour.…”
Section: -2supporting
confidence: 86%
See 2 more Smart Citations
“…There is also a decreasing trend in impact strength with increasing CaCO3 content. This trend has also been observed by Basilia et al [3] with different matrices. Increased stiffness and hardness caused by filler presence may have favoured crack propagation upon impact, and composite specimen will absorb less energy than the neat polymer, causing a more brittle behaviour.…”
Section: -2supporting
confidence: 86%
“…However, DSC revealed decrease in degree of crystallinity for almost all composites in relation to unfilled PA6, as shown in Table 1. Basilia et al [3] have observed similar behavior and credited it to the fact that the presence of the filler particles may hinder polymer chain packing. …”
Section: -3mentioning
confidence: 79%
See 1 more Smart Citation
“…CaCO 3 with a few weight percentages loading in the thermoplastic polymer nanocomposites strongly effects on properties of polymers. 1 –7 The effects of addition of precipitated CaCO 3 (PCC) to thermoplastic polymers have been investigated by many researchers. The results showed that the significant improvements have been shown in thermal and mechanical properties, such as higher heat distortion temperatures, an enhancement in flame resistance, increase in modulus, stiffness, better barrier properties, enhancements of viscosity, and dimensional stability.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the significant improvements have been shown in thermal and mechanical properties, such as higher heat distortion temperatures, an enhancement in flame resistance, increase in modulus, stiffness, better barrier properties, enhancements of viscosity, and dimensional stability. 1 –7…”
Section: Introductionmentioning
confidence: 99%